2019
DOI: 10.3324/haematol.2019.217430
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is over-expressed in leukemic cells from TP53-disrupted patients and is a promising therapeutic target in chronic lymphocytic leukemia

Abstract: HIF-1a is overexpressed in leukemic cells from TP53-disrupted patients and is a promising therapeutic target in chronic lymphocytic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 46 publications
5
56
0
Order By: Relevance
“…and Expression in a VHL-Dependent Manner. Accumulated evidence has demonstrated that HIF-1α has a dominant role in tumor progression, and HIF-1α-regulation of expression of VEGFA is regarded as the main inducer of angiogenesis [27][28][29]. In the current study, we hypothesized if meloxicam 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 Oxidative Medicine and Cellular Longevity could inhibit HIF-1α expression and its target gene VEGFA.…”
Section: Meloxicam Downregulates Hif-1α Transcription Activitymentioning
confidence: 99%
“…and Expression in a VHL-Dependent Manner. Accumulated evidence has demonstrated that HIF-1α has a dominant role in tumor progression, and HIF-1α-regulation of expression of VEGFA is regarded as the main inducer of angiogenesis [27][28][29]. In the current study, we hypothesized if meloxicam 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 10 4 10 3 10 2 10 1 10 0 Oxidative Medicine and Cellular Longevity could inhibit HIF-1α expression and its target gene VEGFA.…”
Section: Meloxicam Downregulates Hif-1α Transcription Activitymentioning
confidence: 99%
“…The HIF-1α pathway generally involves chondrogenesis and cartilage formation of chondrocytes (16). BAY-87-2243 is a potent and selective HIF-1α blocker and inhibitor (26,27), it is suggested that BAY-87-2243 could block of HIF-1α expression mediated IL-17 and CoCl 2 in RAW 264.7 macrophage cells (27). Although it is known that BA has a protective effect on chondrocytes, the effect and mechanism of BA on the HIF-1α pathway in chondrocytes has not yet been elucidated.…”
Section: Baicalin Promotes Extracellular Matrix Synthesis In Chondrocmentioning
confidence: 99%
“…In this issue of Haematologica, Griggio et al report that disrupting mutations in the tumor-suppressor gene TP53 are associated with higher HIF-1α levels and activity in patients with chronic lymphocytic leukemia (CLL). 3 They further show that elevated HIF-1α levels are due to an increased transcription as well as a decreased protein degradation of HIF-1α. Evidence for both regulatory mechanisms have already been described in CLL and are summarized in Figure 1.…”
mentioning
confidence: 95%
“…In line with this, Griggio et al observed increased expression of HIF-1α in CLL cells upon co-culture with stromal cells to a level that is comparable to hypoxic conditions. 3 They further showed that HIF-1α transcript levels of primary CLL cells positively correlate with CLL cell survival in culture. This is likely related to the observation that HIF-1α critically regulates the interaction of CLL cells with their microenvironment.…”
mentioning
confidence: 97%
See 1 more Smart Citation